The Use of Fly Ash as Additive Material to High Strength Concrete - Pangestuti, Endah Kanti; Handayani, Sri; Purnomo, Mego; Silitonga, Desi Christine; Fathoni, M. Hilmy (Jurnal Teknik Sipil dan Perencanaan, 2018)
Abstract. The use of coal waste (Fly Ash) is currently being developed in building materials technology, as a high-strength concrete mix material. This study aims to determine the strength of concrete by adding fly ash as a substitute for cement in high-strength concrete mixtures. This research was conducted with an experimental method to obtain results and data that would confirm the variables studied. The total number of specimens used in this study were 36 pieces with different sizes of cube tests which were 15 cm x 15 cm x 15 cm. A total of 36 concrete samples were used to test the compressive strength of concrete with a percentage of Fly Ash inÃ‚Â  0% (normal concrete), 20%, 25% and 30% with a concrete treatment age of 7 days, 21 days and 28 days. A total of 12 more samples were used to test water absorption in concrete at 28 days of maintenance. Each percentage percentage of Fly Ash uses 3 concrete test samples. The increase in compressive strength occurs at 7, 21 and 28 days in concrete. However, the compressive strength of concrete produced by concrete using the percentage of Fly Ash is always lower than the value of normal concrete compressive strength. From testing the compressive strength of concrete at 28 days of treatment with content of 0%, 20%, 25% and 30% Fly Ash obtained results of 45.87 MPa, 42.67 MPa, 40.89 MPa, and 35.27 MPa respectively